Clinical Presentation and Outcome of Insect Bite in A Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Human contact with insects is unavoidable. Exposure to biting or stinging insects or their remains can range from benign or barely noticeable to lifethreatening. The study aimed to explore the clinical presentation and outcome of the patients admitted to a tertiary-level hospital due to insect bites.Materials and methods: This prospective observational study included 100 insect bite patients admitted to the Chittagong Medical College Hospital from July to December 2015. Data regarding socio-demographic profiles, types of insects, clinical profiles, complications, and in-hospital outcomes were collected using a structured case record form.Results: The mean age of the patients was 37.3 (± 4.4) years (Range: 1.5 – 80 years) and 72% were male. Most of the patients (82%) were rural residents. Nearly threequarters (73%) of biting or stinging incidents were caused by Hymenoptera (wasp, bee, and ant), followed by centipedes (23%). Redness (95%), swelling (83%) and itching (45%) were the common presenting features. Abnormal biochemical parameters were raised serum creatinine (5%), raised CPK (1%), moderate presenting anemia (1%), raised serum bilirubin (1%), increased prothrombin time (1%), and raised serum ALT (1%). The majority (95%) of the patients recovered uneventfully; only one patient died due to multi-organ failure.Conclusion: Though recovery from insect bite was uneventful, few patients had acute kidney injury.JCMCTA 2022 ; 33 (2) : 14-17